A multi-level pore composite molecular sieve, preparation method and application thereof

By preparing multi-stage pore composite molecular sieve, the problem that the existing ZSM-5 molecular sieve is difficult to enter the microporous channel in the catalytic cracking of heavy oil, and the effect of improving conversion and propylene yield is achieved.

CN119746919APending Publication Date: 2025-04-04SHANDONG CHAMBROAD PETROCHEMICALS CO LTD

Patent Information

Application Number
CN202411934356.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the catalytic cracking of heavy oil, existing ZSM-5 molecular sieves have problems with macromolecular heavy oil components that are difficult to enter the microporous channel, resulting in reduced accessibility of acid sites and reduced propylene selectivity.

Method used

The preparation method of multi-stage pore composite molecular sieve is adopted to obtain microspheres by spray molding, and then mixed with silicon source, aluminum source and mesoporous guide agent after calcination and activation, and then crystallized under the action of a template agent to obtain ZSM-5 molecular sieve with a multi-stage pore structure.

Benefits of technology

The conversion rate of heavy oil catalytic cracking reaction and the yield of propylene are improved, the utilization rate of acidic sites and the diffusion ability of product molecules are enhanced, and the production of coke is inhibited.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211132950000091
    Figure BDA0005211132950000091
  • Figure BDA0005211132950000101
    Figure BDA0005211132950000101
  • Figure BDA0005211132950000102
    Figure BDA0005211132950000102
Patent Text Reader

Abstract

The present invention provides a method for preparing a multi-level porous composite molecular sieve, comprising the following steps: S1) mixing a binder, a carrier, a mesoporous directing agent and water, and spraying to obtain microspheres; S2) mixing the microspheres with a silicon source, an aluminum source and a mesoporous directing agent after calcination, and calcining and activating again; S3) mixing the microspheres obtained in step S2) with a template agent and water for synthesizing a ZSM-5 molecular sieve, and calcining the solid product obtained after crystallization to obtain a multi-level porous composite molecular sieve. The present application also provides a multi-level porous composite molecular sieve and its application. The composite molecular sieve provided in the present application can be applied to fields such as heavy oil catalytic cracking, effectively improving the diffusion of catalyst acid sites and substrate molecules and product molecules in the reaction, improving the reaction conversion rate and inhibiting coke formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy oil catalytic cracking, and in particular to a multi-level pore composite molecular sieve, a preparation method thereof and application thereof. Background Art

[0002] Fluidized catalytic cracking (FCC) is the core technology of modern oil refining industry, which is mainly used to convert high boiling point and high molecular weight petroleum fractions into more valuable fuels, such as gasoline, diesel, liquefied petroleum gas (LPG) and olefins. ZSM-5 molecular sieve has a unique pore structure and is widely used in heavy oil catalytic cracking catalysts to increase the content of light olefins in the product. However, the ZSM-5 molecular sieve with octahedral microporous structure has two major drawbacks: first, it is difficult for large molecular heavy oil components to enter the micropores of ZSM-5 molecular sieve, resulting in reduced accessibility of acid sites of ZSM-5 molecular sieve and decreased reaction conversion rate; second, the narrow pores limit the migration of reaction products, increase the possibility of secondary reactions, and reduce propylene selectivity. Therefore, introducing mesopores into heavy oil catalytic cracking catalysts is an effective way to solve the above problems.

[0003] The Chinese patent with publication number CN117696104A discloses a catalyst with a core-shell structure, wherein the core has a catalytic cracking function and the shell has a catalytic dehydrogenation function; the catalyst comprises the following components in weight percentage on a dry basis: 5-65% molecular sieve; 10-70% oxide binder; 10-70% natural minerals; 0.05-70% metal oxide; wherein 10-70% oxide binder means that the oxide in the oxide binder accounts for 10-70% of the total dry basis of the catalyst; the core of the catalyst has acid catalytic cracking activity and the shell has catalytic dehydrogenation activity, which is beneficial to improving the conversion rate and propylene yield.

[0004] The Chinese patent with publication number CN117019232A provides a preparation method and application of a multi-level porous catalyst, which includes the following steps: mixing water, a structure directing agent, an alkali source, an aluminum source and a silicon source to obtain a mixture A; mixing the mixture A with a porogen and a seed to obtain a mixture B; filtering, washing, drying and roasting the product after the crystallization treatment of the mixture B to obtain a multi-level porous ZSM-5 molecular sieve; mixing the multi-level porous ZSM-5 molecular sieve with water, ball milling and uniformly obtaining a slurry C; mixing the slurry C with kaolin and aluminum sol to obtain a slurry D; mixing the slurry D with pseudo-boehmite to obtain a slurry E; adding hydrochloric acid to the slurry E to acidify it to obtain a slurry F; mixing the slurry F with a phosphorus precursor to obtain a slurry G; ball milling the slurry G and spraying it to obtain microsphere particles; drying and roasting the microsphere particles to obtain a catalyst. The catalyst exhibits high activity in catalytic cracking, good selectivity, and is easy to industrialize.

[0005] It can be seen from the above patents that in the current research related to catalytic cracking, the introduction of mesopores in the catalyst is beneficial to the catalytic cracking reaction of heavy oil; although the molecular sieve microsphere catalyst obtained by the in-situ crystallization process is complex and costly, it has better accessibility to active components in the catalytic cracking reaction of heavy oil, and due to the introduction of mesopores, it can give full play to its catalytic performance, greatly improve the conversion rate and propylene selectivity of the catalytic cracking reaction of heavy oil, and inhibit coking. However, the above catalysts are limited in improving the conversion rate and propylene selectivity of the catalytic cracking reaction of heavy oil, and need to be further improved. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a multi-level pore composite molecular sieve. The multi-level pore composite molecular sieve provided by the present application is used as a catalyst for catalytic cracking of heavy oil to achieve a conversion rate and a yield of propylene.

[0007] In view of this, the present application provides a method for preparing a multi-level pore composite molecular sieve, comprising the following steps:

[0008] S1) mixing a binder, a carrier, a mesopore directing agent and water, and spraying to obtain microspheres;

[0009] S2) mixing the calcined microspheres with a silicon source, an aluminum source, and a mesopore directing agent, and calcining again for activation;

[0010] S3) mixing the microspheres obtained in step S2) with a template for synthesizing a ZSM-5 molecular sieve and water, and calcining the solid product obtained after crystallization to obtain a multi-level porous composite molecular sieve.

[0011] Preferably, in step S1), the binder includes one or more of aluminum sol, silica sol, phosphate aluminum colloid, acidified pseudo-boehmite and water glass, the carrier is selected from an inert matrix, and the inert matrix includes one or more of kaolin, bentonite and attapulgite; the mesoporous directing agent includes one or more of hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch and mesoporous carbon spheres; the mass ratio of the binder to the carrier is (0.1-0.5):1, and the mass ratio of the carrier to the mesoporous directing agent is (3-10):1.

[0012] Preferably, in step S2), the microspheres are calcined by rotary calcination, the calcination temperature is 200-500°C, and the time is 0.1-10h; the size of the microspheres is 20-150μm; the silicon source includes one or more of silicon tetrachloride, tetraethyl orthosilicate, vinyl silane, aminosilane and silica sol; the aluminum source includes one or more of sodium aluminate, aluminum hydroxide, aluminum sulfate and pseudo-boehmite, and the mesoporous directing agent includes one or more of hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch and mesoporous carbon spheres; the mass ratio of the sum of the silicon source and the aluminum source, the mesoporous directing agent and the microspheres is 1-10:0.01-0.1:1; the temperature of the re-calcination activation is 200-500°C, and the time is 0.1-10h.

[0013] Preferably, in step S3), the template agent includes one or more of n-butylamine, triethylamine, tetrapropylammonium hydroxide, tetramethylammonium hydroxide and tetrabutylammonium hydroxide.

[0014] Preferably, in step S3), the mass ratio of the template to the microspheres is (0.01-1):1, the solid content of the mixture obtained by the microspheres, the template and the water is 10-80%; the crystallization temperature is 100-200°C, and the time is 1-40h.

[0015] Preferably, in step S3), the calcination further comprises solid-liquid separation, water washing and drying in sequence, and the drying temperature is 50-150°C.

[0016] Preferably, in step S3), the calcination temperature is 500-800° C. and the calcination time is 1-10 h.

[0017] The present application also provides a multi-level porous composite molecular sieve prepared by the preparation method, which is composed of mesoporous carrier microspheres and a multi-level porous ZSM-5 molecular sieve coated on the surface of the mesoporous carrier microspheres.

[0018] Preferably, the size of the mesoporous carrier microspheres is 20 to 150 μm, the multi-level pore ZSM-5 molecular sieve includes micropores and mesopores, the pore size of the micropores is less than 2 nm, and the pore size of the mesopores is 2 to 50 nm.

[0019] The present application also provides the multi-level pore composite molecular sieve prepared by the preparation method or the use of the multi-level pore composite molecular sieve as a catalyst in the field of heavy oil catalytic cracking.

[0020] The present application provides a method for preparing a multi-level porous composite molecular sieve, which first sprays a binder, a carrier and a mesoporous directing agent to obtain microspheres, then roasts the microspheres to obtain carrier microspheres with mesopores, and then, after roasting and activating the carrier microspheres with a silicon source, an aluminum source and a mesoporous directing agent, a ZSM-5 molecular sieve coating layer with multi-level pores is obtained under the action of a template agent. The multi-level porous composite molecular sieve prepared in the present application consists of mesoporous carrier microspheres and multi-level porous ZSM-5 molecular sieves coated on the surface of the mesoporous carrier microspheres. The composite material has the characteristics of high specific surface area and large pore volume, and therefore can be used as a catalyst for catalytic cracking of heavy oil to improve the conversion rate and the yield of propylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD spectrum of the multi-level pore composite molecular sieve prepared in the embodiment of the present invention;

[0022] Figure 2 This is a SEM photograph of the multi-level pore composite molecular sieve prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0023] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0024] In view of the demand for heavy oil catalytic cracking catalysts in the prior art, the present application provides a multi-level pore composite molecular sieve and a preparation method thereof. The composite molecular sieve can be used as a catalyst for heavy oil catalytic cracking, effectively improving the utilization rate of acid sites and the diffusion of substrate molecules and product molecules in the reaction, improving the reaction conversion rate and inhibiting the generation of coke. Specifically, the embodiment of the present invention discloses a preparation method of a multi-level pore composite molecular sieve, comprising the following steps:

[0025] S1) mixing a binder, a carrier, a mesopore directing agent and water, and spraying to obtain microspheres;

[0026] S2) mixing the calcined microspheres with a silicon source, an aluminum source, and a mesopore directing agent, and calcining again for activation;

[0027] S3) mixing the microspheres obtained in step S2) with a template for synthesizing a ZSM-5 molecular sieve and water, and calcining the solid product obtained after crystallization to obtain a multi-level porous composite molecular sieve.

[0028] In the preparation process of multi-level porous composite molecular sieve, the present application first mixes the binder, carrier, mesoporous directing agent and water, and obtains microspheres after spray molding; in this process, the binder, carrier, mesoporous directing agent and water are mixed and slurried, and then spray molded to obtain microspheres; the above-mentioned mixed slurry can be mechanically ground to ensure that the slurry is fully mixed, such as using a ball mill, the ball milling rate is 200-500rpm, and the time is 0.5-1h. The binder includes one or more of aluminum sol, silica sol, phosphate aluminum colloid, acidified pseudo-boehmite and water glass. Specifically, the binder is selected from aluminum sol. The carrier is selected from an inert matrix, and the inert matrix includes one or more of kaolin, bentonite and attapulgite. Specifically, the carrier is selected from kaolin. The mesoporous directing agent includes one or more of hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch and mesoporous carbon spheres. Specifically, the mesoporous directing agent is selected from hexadecyltrimethylammonium bromide, polyethylene glycol 10000, starch or mesoporous carbon spheres with a size of 200 to 400 nm. On an oxide dry basis, the mass ratio of the binder to the carrier is (0.1 to 0.5):1. Specifically, the mass ratio of the binder to the carrier is (0.2 to 0.4):1. The mass ratio of the carrier to the mesoporous directing agent is (3 to 10):1. Specifically, the mass ratio of the carrier to the mesoporous directing agent is (3.5 to 9):1. More specifically, the mass ratio of the binder to the mesoporous directing agent is (4.5 to 8.5):1.

[0029] According to the present invention, mesoporous carrier microspheres are obtained after calcining the above microspheres, that is, mesopores exist in the carrier microspheres; the calcination is specifically rotary calcination, the temperature of the rotary calcination is 200-400°C, and the time is 0.1-10h; specifically, the temperature of the calcination is 250-350°C, and the time is 1-5h. The obtained microspheres are then mixed with a silicon source, an aluminum source, and a mesoporous directing agent, and calcined again for activation; in this process, the silicon source and the aluminum source are raw materials that can form a ZSM-5 molecular sieve, specifically, the silicon source is selected from one or more of silicon tetrachloride, tetraethyl orthosilicate, vinyl silane, aminosilane, and silica sol; specifically, the silicon source is selected from one or more of silicon tetrachloride, tetraethyl orthosilicate, silica sol, vinyl trimethoxysilane, or vinyl triethoxysilane. The aluminum source includes one or more of sodium aluminate, aluminum hydroxide, aluminum sulfate, and pseudo-boehmite, specifically, the aluminum source includes sodium aluminate, aluminum hydroxide, aluminum sulfate octahydrate, or pseudo-boehmite. The mesoporous directing agent comprises one or more of hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch and mesoporous carbon spheres; specifically, the mesoporous directing agent is selected from hexadecyltrimethylammonium bromide, polyethylene glycol 10000, starch or mesoporous carbon spheres with a size of 200-400 nm. On a dry basis of oxides, the sum of the silicon source and the aluminum source, the mass ratio of the mesoporous directing agent to the microspheres is 1-10:0.01-0.1:1, specifically, the sum of the silicon source and the aluminum source, the mass ratio of the mesoporous directing agent to the microspheres is 2-8:0.03-0.07:1. The temperature of the re-calcination activation is 200-500°C, and the time is 0.1-10h; specifically, the temperature of the re-calcination activation is 300-400°C, and the time is 1-5h.

[0030] Finally, the present application mixes the microspheres obtained above with the template agent and water for synthesizing ZSM-5 molecular sieve, and the solid product obtained after crystallization is calcined to obtain a multi-level porous composite molecular sieve. The above template agent is introduced to ensure that the ZSM-5 molecular sieve is obtained; specifically, it is selected from one or more of n-butylamine, triethylamine, tetrapropylammonium hydroxide, tetramethylammonium hydroxide and tetrabutylammonium hydroxide. More specifically, the template agent is selected from tetrapropylammonium hydroxide, n-butylamine, triethylamine, tetramethylammonium hydroxide or tetrabutylammonium hydroxide. The mass ratio of the template agent (effective component organic amine) and the microsphere (oxide dry basis) is (0.01-1):1, specifically, the mass ratio of the template agent and the microsphere is (0.1-0.7):1; the solid content of the mixture obtained by the microsphere, the template agent and the water is 10-80%, specifically, the solid content of the mixture obtained by the microsphere, the template agent and the water is 20-60%. The crystallization temperature is 100-200°C and the time is 1-30h; specifically, the crystallization temperature is 120-170°C and the time is 24-36h. The calcination temperature is 500-800°C and the time is 1-10h. Specifically, the calcination temperature is 600-700°C and the time is 4-8h. Before calcination, it is also preferred to sequentially perform solid-liquid separation, water washing and drying on the solid product. The solid-liquid separation can be performed by suction filtration, centrifugation and the like, and the drying can be performed by blast drying, vacuum drying and the like.

[0031] In the present application, the oxide dry basis specifically refers to: part of the raw materials used to synthesize the multi-level porous composite molecular sieve will form a combination structure of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron after reaction, and for the convenience of calculation, it is calculated based on silicon oxide and aluminum oxide.

[0032] The present application also provides a multi-level porous composite molecular sieve prepared by the above preparation method, which is composed of mesoporous carrier microspheres and a multi-level porous ZSM-5 molecular sieve coated on the surface of the mesoporous carrier microspheres.

[0033] In the multi-level pore composite molecular sieve, the size of the mesoporous carrier microspheres is 20-150 μm, and mesopores are distributed therein; the multi-level pore ZSM-5 molecular sieve includes micropores and mesopores, the pore size of the micropores is less than 2 nm, and the pore size of the mesopores is 2-50 nm.

[0034] Furthermore, the present application also provides the use of the above-mentioned multi-level pore composite molecular sieve as a catalyst in the field of heavy oil catalytic cracking.

[0035] In order to further understand the present invention, the multi-level pore composite molecular sieve provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0036] Example 1

[0037] (1) 900 g of kaolin, 100 g of hexadecyltrimethylammonium bromide and 500 g of aluminum sol (20 wt%) were added to 1100 g of deionized water and stirred for 1 h. After being mixed evenly, the mixture was formed by a high-temperature spray centrifugal device to obtain microsphere particles;

[0038] (2) placing the obtained microsphere particles in a tube furnace at 250° C. and rotating and calcining for 1 h, during which a mixed solution of 60 g of tetraethyl orthosilicate, 0.78 g of sodium aluminate and 14 g of hexadecyltrimethylammonium bromide was introduced into the tube furnace at a rate of 1 g / min to obtain calcined activated microspheres;

[0039] (3) 8 g of 25% tetrapropylammonium hydroxide solution and 800 g of deionized water were mixed, and then the calcined activated microspheres were added, stirred for 30 min, and then placed in a kettle for crystallization at 170° C. for 36 h;

[0040] (4) The crystallized solid product was washed, dried at 100° C., and calcined at 600° C. for 4 hours to obtain a multi-level porous composite molecular sieve catalyst.

[0041] Example 2

[0042] (1) 900 g of kaolin, 120 g of polyethylene glycol 10000 and 500 g of aluminum sol (20 wt%) were added to 1100 g of deionized water and stirred for 1 h. After being mixed evenly, the mixture was formed using a high-temperature spray centrifugal device to obtain microsphere particles;

[0043] (2) placing the obtained microsphere particles in a tube furnace at 250° C. and rotating and calcining for 1 h, during which a mixture of 49 g of silicon tetrachloride, 1.5 g of aluminum hydroxide and 18 g of polyethylene glycol 10000 was introduced into the tube furnace at a rate of 1 g / min to obtain calcined activated microspheres;

[0044] (3) 7.2 g of n-butylamine and 800 g of deionized water were mixed, and then the calcined activated microspheres were added, stirred for 30 min, and then placed in a kettle for crystallization at 170 ° C for 36 h;

[0045] (4) The crystallized solid product was washed, dried at 100° C., and calcined at 600° C. for 4 hours to obtain a multi-level porous composite molecular sieve catalyst.

[0046] Example 3

[0047] (1) 900 g of kaolin, 240 g of polyethylene glycol 10000 and 500 g of aluminum sol (20 wt%) were added to 1100 g of deionized water and stirred for 1 h. After being mixed evenly, the mixture was formed using a high-temperature spray centrifugal device to obtain microsphere particles;

[0048] (2) placing the obtained microsphere particles in a tube furnace at 250° C. and rotating and calcining for 1 h, during which a mixed solution of 57.6 g of silica sol, 6.4 g of aluminum sulfate 18hydrate and 36 g of polyethylene glycol 10000 was introduced into the tube furnace at a rate of 1 g / min to obtain calcined activated microspheres;

[0049] (3) 10 g of triethylamine and 800 g of deionized water were mixed, and then the calcined activated microspheres were added, stirred for 30 min, and then placed in a kettle for crystallization at 170 ° C for 36 h;

[0050] (4) The crystallized solid product was washed, dried at 100° C., and calcined at 600° C. for 4 hours to obtain a multi-level porous composite molecular sieve catalyst.

[0051] Example 4

[0052] (1) 900 g of kaolin, 110 g of starch and 500 g of aluminum sol (20 wt%) were added to 1100 g of deionized water and stirred for 1 h. After being mixed evenly, the mixture was formed using a high-temperature spray centrifugal device to obtain microsphere particles;

[0053] (2) placing the obtained microsphere particles in a tube furnace at 250° C. and rotating and calcining for 1 h, during the calcining process, a mixture of 42.7 g of vinyltrimethoxysilane, 0.64 g of pseudoboehmite and 15 g of starch was introduced into the tube furnace at a rate of 1 g / min to obtain calcined activated microspheres;

[0054] (3) 36 g of 25% tetramethylammonium hydroxide solution and 800 g of deionized water were mixed, and then the calcined activated microspheres were added, stirred for 30 min, and then placed in a kettle for crystallization at 170° C. for 36 h;

[0055] (4) The crystallized solid product was washed, dried at 100° C., and calcined at 600° C. for 4 hours to obtain a multi-level porous composite molecular sieve catalyst.

[0056] Example 5

[0057] (1) 900 g of kaolin, 200 g of mesoporous carbon spheres (200-400 nm) and 500 g of aluminum sol (20 wt%) were added to 1100 g of deionized water and stirred for 1 h. After being mixed evenly, the mixture was formed using a high-temperature spray centrifugal device to obtain microsphere particles;

[0058] (2) placing the obtained microsphere particles in a tube furnace at 250° C. and rotating and calcining for 1 h, during which a suspension of 54.8 g of vinyltriethoxysilane and 20 g of mesoporous carbon spheres (200-400 nm) was introduced into the tube furnace at a rate of 1 g / min to obtain calcined activated microspheres;

[0059] (3) 102 g of 25% tetrabutylammonium hydroxide solution and 800 g of deionized water were mixed, and then the calcined activated microspheres were added, stirred for 30 min, and then placed in a kettle for crystallization at 170° C. for 36 h;

[0060] (4) The crystallized solid product was washed, dried at 100° C., and calcined at 600° C. for 4 hours to obtain a multi-level porous composite molecular sieve catalyst.

[0061] Figure 1 The XRD patterns of the multi-level porous composite molecular sieve catalysts prepared in Examples 1 to 5 are as follows: Figure 1 It can be seen that the multi-level porous composite molecular sieve prepared in this application has a typical MFI structure; for example, the scanning electron microscope images of the multi-level porous composite molecular sieve catalysts prepared in Examples 1 to 5 are as follows: Figure 2 As shown, the catalyst is ellipsoidal as a whole, and the ZSM-5 molecular sieve is distributed on the outer surface of the matrix, which is beneficial to improving the accessibility of the reaction active center.

[0062] The characteristics of the multi-level pore composite molecular sieve prepared in Example were detected, and the results are shown in Table 1;

[0063] Table 1 Catalyst surface area and pore volume test results

[0064]

[0065] It can be seen from the surface area and pore volume test results of the multi-level porous composite molecular sieves prepared in Examples 1 to 5 that the catalyst materials prepared using hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch, and mesoporous carbon spheres (200-400nm) as mesopore directing agents respectively have abundant micropores and mesoporous structures; and due to the different volumes or properties of different mesopore directing agents, the mesoporous structures they guide are different.

[0066] The catalyst was loaded into a fixed fluidized bed for evaluation, and the performance of the catalyst prepared in each embodiment in the heavy oil catalytic cracking reaction process was investigated; the experimental raw oil was atmospheric wax oil from a refinery in Shandong, and its physical properties are shown in Table 2. During the reaction, the catalyst loading amount was 200 g, and the feed space velocity was 3 h -1 , steam dilution ratio 1, reaction temperature 550°C, test results are shown in Table 3;

[0067] Table 2 Physical property index data of crude oil

[0068]

[0069] Table 3 Physical properties and catalytic performance data of samples in the examples

[0070]

[0071] In the heavy oil catalytic cracking reaction, the catalyst with mesopores is conducive to the rapid diffusion of heavy oil macromolecules, improves the utilization rate of acid sites, and is more conducive to the rapid contact and separation of macromolecular substrates and products with active sites, which can effectively improve the yield of dienes, prevent secondary reactions, and reduce the generation of carbon deposits. It can be seen from Tables 2 and 3 that with the increase of mesopores, the propylene yield gradually increases.

[0072] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0073] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a multi-level porous composite molecular sieve, comprising the following steps: S1) mixing a binder, a carrier, a mesopore directing agent and water, and spraying to obtain microspheres; S2) mixing the calcined microspheres with a silicon source, an aluminum source, and a mesopore directing agent, and calcining again for activation; S3) mixing the microspheres obtained in step S2) with a template for synthesizing a ZSM-5 molecular sieve and water, and calcining the solid product obtained after crystallization to obtain a multi-level porous composite molecular sieve.

2. The preparation method according to claim 1, characterized in that: In step S1), the binder includes one or more of aluminum sol, silica sol, phosphate aluminum colloid, acidified pseudo-boehmite and water glass, the carrier is selected from an inert matrix, and the inert matrix includes one or more of kaolin, bentonite and attapulgite; the mesoporous directing agent includes one or more of hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch and mesoporous carbon spheres; the mass ratio of the binder to the carrier is (0.1-0.5):1, and the mass ratio of the carrier to the mesoporous directing agent is (3-10):

1.

3. The preparation method according to claim 1, characterized in that: In step S2), the microspheres are calcined by rotary calcination, the calcination temperature is 200-500°C, and the time is 0.1-10h; the size of the microspheres is 20-150μm; the silicon source includes one or more of silicon tetrachloride, tetraethyl orthosilicate, vinyl silane, aminosilane and silica sol; the aluminum source includes one or more of sodium aluminate, aluminum hydroxide, aluminum sulfate and pseudo-boehmite, and the mesoporous directing agent includes one or more of hexadecyltrimethylammonium bromide, polyethylene glycol 10000, polyethylene glycol 20000, starch and mesoporous carbon spheres; the mass ratio of the sum of the silicon source and the aluminum source, the mesoporous directing agent and the microspheres is 1-10:0.01-0.1:1; the temperature of the re-calcination activation is 200-500°C, and the time is 0.1-10h.

4. The preparation method according to claim 1, characterized in that: In step S3), the template agent includes one or more of n-butylamine, triethylamine, tetrapropylammonium hydroxide, tetramethylammonium hydroxide and tetrabutylammonium hydroxide.

5. The preparation method according to claim 1, characterized in that: In step S3), the mass ratio of the template to the microsphere is (0.01-1):1, the solid content of the mixture obtained by the microsphere, the template and the water is 10-80%; the crystallization temperature is 100-200°C, and the time is 1-40h.

6. The preparation method according to claim 1, characterized in that: In step S3), before the calcination, solid-liquid separation, water washing and drying are sequentially performed, and the drying temperature is 50-150°C.

7. The preparation method according to claim 1, characterized in that: In step S3), the calcination temperature is 500-800° C. and the calcination time is 1-10 hours.

8. The multi-level porous composite molecular sieve prepared by the preparation method according to any one of claims 1 to 7, which is composed of mesoporous carrier microspheres and multi-level porous ZSM-5 molecular sieves coated on the surface of the mesoporous carrier microspheres.

9. The multi-level pore composite molecular sieve according to claim 7, characterized in that: The size of the mesoporous carrier microspheres is 20-150 μm, the multi-level pore ZSM-5 molecular sieve includes micropores and mesopores, the pore diameter of the micropores is less than 2 nm, and the pore diameter of the mesopores is 2-50 nm.

10. Use of the multi-level pore composite molecular sieve prepared by the preparation method according to any one of claims 1 to 6 or the multi-level pore composite molecular sieve according to any one of claims 7 to 9 as a catalyst in the field of heavy oil catalytic cracking.

Citation Information

Patent Citations

  • Preparation method and application of diesel catalytic cracking catalyst

    CN117019232A

  • Straight-run diesel oil catalytic cracking catalyst and preparation method thereof

    CN117696104A

Cited By

  • Preparation method of hierarchical pore molecular sieve and characterization method of Ce setting condition in molecular sieve

    CN120757125A

  • Preparation method of flaky mesoporous material with specific surface area and mechanical strength

    CN121247832A

  • Preparation method of flaky mesoporous material with consideration of specific surface area and mechanical strength

    CN121247832B